Elementary school students' numeracy ability in a socio-cultural context viewed by understanding mathematical concepts - Anis Rosiatul Chusna; Via Yustitia (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
This research aims to (1) Describe the numeracy of students with high, (2) Describe the numeracy of students with medium, and (3) Describe the numeracy of students with low understanding of mathematical concepts. The selected subjects were 3 out of 29 class 5B students at SDN Rungkut Menanggal II Surabaya. Tests and interviews served as the instrument. The data analysis is data condensation, data presentation, and conclusion. The results of this research are (1) The numeracy of high and medium students' concept understanding; they have been able to apply the formulating process; in the process of using, students are not yet able to determine strategies, are not able to apply concepts, are not able to do calculations; In the interpreting process, students are not yet able to evaluate mathematical results and conclusions. (2) The numeracy of low students' understanding concepts, it was found that students were able to formulate; in the process of using, students can determine strategies, are not yet able to apply concepts, can do calculations; in the process of interpreting students are not yet able to evaluate the results and conclusions of statements.